Development Of Interactive Learning Applications Based On Artificial Intelligence To Improve Early Childhood Literacy Skills At RA Darussalam 009 - Purwandari, Nuraini; Nasution, Taruna (Publisher Cv. Inara, 2025)
Early childhood literacy skills are an important foundation in children's cognitive and academic development in the future. However, in RA Darussalam 009 it was found that conventional learning methods are still not optimal in stimulating children's interest and understanding of letters and words. This research aims to develop an interactive learning application based on artificial intelligence (AI) to improve early childhood literacy skills. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The application is designed with voice recognition, image recognition, and automatic response features using simple Natural Language Processing (NLP) that are adjusted to the child's age. Testing was conducted on 25 children aged 4–6 years. The results of the research showed that the use of this application provided a significant increase in the ability to recognize letters, read simple words, and participate actively in the learning process. The results of this research indicate that AI technology can be effectively adapted in early childhood education environments to support fun, interactive, and adaptive learning to children's needs.